Further Development of the Tin-Catalyzed Transcarbamoylation Reaction - Ichikawa, Yoshiyasu; Hasegawa, Tomoyuki; Minami, Takahiro; Sato, Hiroshi; Morishita, Yukinori; Ochi, Rika; Masuda, Toshiya (Synthesis, 2020)
Studies carried out to further develop tin-catalyzed transcarbamoylation reactions demonstrated that transcarbamoylation of cinnamyl alcohol in the context of allyl cyanate-to-isocyanate rearrangement can be efficiently carried out on a ten-gram scale and that tin-catalyzed transcarbamoylation is a valuable alternative to the method using trichloroacetyl isocyanate. In addition, methyl carbamate was found to be an economical carabamoyl donor in tin-catalyzed transcarbamoylation, which showed broad functional group tolerance and allowed a streamlined workup procedure. Finally, a unique synthetic method was developed for the preparation of carbamate-tethered terpene glycoconjugates.
Keywords: carbamate; transcarbamoylation; tin; rearrangement; terpenes; glycoconjugates